Strong Convergence of Iterative Algorithm for a New System of Generalized H·,·-η-Cocoercive Operator Inclusions in Banach Spaces - Saud M. Alsulami; Eskandar Naraghirad; Nawab Hussain (Abstract and Applied Analysis)
We introduce and study a new system of generalized H·,·-η-cocoercive operator inclusions in Banach spaces. Using the resolvent operator technique associated with H·,·-η-cocoercive operators, we suggest and analyze a new generalized algorithm of nonlinear set-valued variational inclusions and establish strong convergence of iterative sequences produced by the method. We highlight the applicability of our results by examples in function spaces.